Perceptions towards governance of billfish resource use: The lens of artisanal fishers in Kenya - Damaris Njeri Kinyua; Nelly Isigi Kadagi; Sarah Ater; Melckzedeck Osore; Andrew Wamukota (Frontiers in Marine Science, 2022)
Multiple fisher groups target billfish species, each with different motivations and experiences, which can influence the effectiveness and sustainability of governance approaches. However, limited studies underscore the perceptions of billfish resource users in defining and implementing governance in the Western Indian Ocean region. We conducted 211 semi-structured qualitative interviews between December 2020 and September 2021, to explore how artisanal fishers perceive the performance and sustainability of governance approaches in Kenya, with a focus on billfish. Our findings show that artisanal fishers have adequate knowledge of fishing laws and regulations, as well as governing institutions and their performance. Further, artisanal fishers had a positive attitude and support for fishing rules, managing institutions, and effectiveness of governance intervention. Specifically, the fishers rated Beach Management Units (BMUs) as highly effective in implementing fisheries rules, indicating the involvement of fishers in co-management of fisheries and tendency for governance success and sustainability. This highlights the need to strengthen and support BMUs as an effective governance tool in the co-management of fisheries. We draw attention to our first-time study of the contribution of artisanal billfish fishers to governance of shared fisheries resources. We show that involvement of resource users promotes a bottom-up approach to the co-management of billfish which compliments the current regional and national efforts that have largely focused on commercial fisheries. Our research adds to the scientific body of knowledge on the importance of perceptions in the formation of natural resource governance interventions at varying scales, especially for transboundary species in data-poor areas.